Superselective cannulation of coronary sinus branch with telescopicsystem during left ventricular lead placement - Russo, V.; Nigro, G.; Crescenzo, I. D.; Ammendola, et al., E. (Acta Biomedica Atenei Parmensis, 2009)
We present a case of a 55-year-old man with idiopathic dilated cardiomyopathy, ejection fraction (EF) of 27%, left bundle branch block with QRS duration of 160 ms, NYHA class III, and optimal medical therapy for at least 6 months who was referred to our division for cardiac resynchronization therapy (CRT) using a biventricular pacing device. During the operation, the coronary sinus branch cannulation failed using classical angioplasty guide wire techniques. The pacing lead was successfully implanted into the posterior target vein using a telescopic dual-catheter system.